Zur Bedeutung von σύγκτησις in Inschriften : = Zur Bedeutung von Synktesis in Inschriften - Kaiser, Wolfgang (2021)
Abstract: On the meaning of Synktesis in inscriptions. The paper argues that the word σύγκτησις has the same meaning in inscriptions as in literary sources. Σύγκτησις refers to several contiguous pieces of land owned by one person